The Impact of Broiler Chicken Farming on the Social Environment of the Community in Kampar Utara District, Kampar Regency (A Case Study in Muara Jalai Village, Kampar Utara District, Kampar Regency) - Andika, Muhammad; M. Zaki, M. Zaki; Mahlil, Yusuf; Novita, Maulina; Bachry. H, Syamsul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to determine the community's response to the existence of broiler chicken farm and the impact of broiler chicken farming businesses on the social environment of the community in Muara Jalai Village, North Kampar District. This research was conducted in June in Muara Jalai Village, North Kampar District using qualitative descriptive methods. The results of the research show that the broiler chicken farming business in Muara Jalai Village received various responses from the community, 40% of the respondence feel disturbed and 60% do not feel disturbed by the existence of broiler chicken farming business. There is no negative impact from the broiler chicken farming business on the social community, and no environmental pollution. Fur there more, waste such as feses wich generated from broiler chicken farm did not managed properly, so that make a smelly environment and lots of flies arround the farm area.